Studi Komparatif Aplikasi Tax Treaty Indonesia-Tiongkok Dan Indonesia-Singapura - Aji, Faqih; Irawan, Ferry (WIM Solusi Prima, 2021)
The increasing of global investment and trading has generated a close-relationship among countries. as a sovereign nation, a country will enforce its domestic rules particulary tax law. In order to stabilize the economy and keep the fairness, most countries agree to establish a tax treaty. This research investigates how the impact of tax treaty conducted by Indonesia. In addition, it compares the tax treaty between Indonesia-Chinese and Indonesia-Singapore. This research applies qualitative research to obtain a deep understanding. There are several important findings. First, in general tax treaty can promote a fair taxing for both treaty partners. Second, tax treaty between Indonesia-Singapore is more beneficial compares to Indonesia-Chinese from the perspective of dividend tax rate. Third, the research propose that the Government of Indonesia re-negotiate several articles particularly the tax rate.